Rhodococcus jostii sp. nov., isolated from a medieval grave - Takeuchi, Mariko; Hatano, Kazunori; Sedlácek, Ivo; Pácová, Zdena (International journal of systematic and evolutionary microbiology, 2002)
The taxonomic position of a bacterial strain isolated from the femur of the remains of Jost Lucemburský, margrave in Moravia, Brno (Czech Republic), was investigated by phenotypic, chemotaxonomic and molecular taxonomic methods. The chemotaxonomic characteristics, including the cell-wall amino acid and sugar compositions, the quinone system and the fatty acid profile, were in good agreement with those of the genus Rhodococcus. The G+C content of the DNA was 67.4 mol%. Comparative 16S rRNA gene sequencing demonstrated that the unknown strain represents a distinct line of descent within the genus Rhodococcus. The nearest relatives of the bacterium were Rhodococcus opacus and Rhodococcus percolatus. The unknown bacterium was readily distinguished from these species by using phenotypic methods. On the basis of phylogenetic and phenotypic evidence, it is proposed that the unknown bacterium be classified as Rhodococcus jostii sp. nov. The type strain is strain IFO 16295T (= CCM 4760T).
Keywords: sacharidy; mastné kyseliny; Paleontology; Phenotype; Benzoquinones; Fatty Acids; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; lidé; Molecular Sequence Data; benzochinony; Carbohydrates; zastoupení bazí; Phylogeny; molekulární sekvence - údaje; Czech Republic; buněčná stěna; paleontologie; Base Composition; Česká republika; Rhodococcus; Amino Acids; fenotyp; fylogeneze; aminokyseliny; RNA ribozomální 16S; Cell Wall; Humans